- PENGAKUAN ANAK LUAR KAWIN BERDASARKAN HUKUM PERKAWINAN YANG BERLAKU DI INDONESIA (Studi Putusan Nomor 119/Pdt.P/2022/PN.Njk) : - - Mochammad Maldini Agustian; Setyaningsih (Reformasi Hukum Trisakti, 2023)
Recognition of children out of wedlock is a difference in society related to the absence of regulation on the recognition of children out of wedlock according to the Marriage Law.  Based on Article 43 paragraph (1) Law No. 1 of 1974, the fact is that in society there are still cases of recognition of illegitimate children, one of which is in the decision of the Nganjuk District Court on decision number 119/Pdt.P/2022/PN.Njk.  The main problems in this study are (1) How is the recognition of children out of wedlock according to the marriage law in force in Indonesia?  and (2) Is it in Court decision No.  119/Pdt.P/2022/PN.Njk.  Regarding the recognition of children out of wedlock according to the rules of marriage law that apply in Indonesia?  This study uses a normative type that is descriptive, uses secondary data obtained from literature studies, and the data is processed qualitatively by drawing deductive logical conclusions.  The conclusion of this research is that the recognition of children out of wedlock must comply with the Constitutional Court decision Number 46/PUU-VIII/2010.  The suggestion of this research is that the parties who are going to get married should be carried out in accordance with the laws and regulations that apply in Indonesia so that the marriage that takes place is declared valid in the eyes of the law so that the children born in the marriage have a clear position in the eyes of the law.